In vitro antioxidant, hypotensive and diuretic activities of Origanum glandulosum in rat (Bangladesh Journal of Pharmacology, 2019)
The objective of this study was to evaluate the in vitro antioxidant, hypotensive and the diuretic activities of Origanum glandulosum leaves in rat. Chemical analysis revealed the isolation of katuranin and 5-isopropyl-3-methylphenol. Ethyl acetate extract possessed highest scavenging activity against DPPH and hydroxyl radicals. Intravenous administration of extracts (0.04 to 12 mg/kg body weight) dose-dependently decreased the blood pressure (systolic, diastolic and mean) of the anesthetized rat. Methanol extract showed dose-dependent diuretic activity by increasing the urine output (77%) and the urinary excretion of sodium and potassium. In conclusion, this study supports the use of O. glansulosum in traditional medicine as hypotensive and diuretic agents.Video Clip of Methodology:DPPH radical scavenging assay: 4 min 45 sec: Click to watch